Pomiar i ocena jakości usług z zastosowaniem liczb rozmytych - Kusterka-Jefmańska, Marta; Jefmański, Bartłomiej (Measuring and Assessing the Quality of Services with the Use of Fuzzy Numbers, 2009)
The aim of the study is to present a method of measuring and assessing the quality of services based on using fuzzy figures. The presented method is an alternative to methods which have been used in measuring and assessing the quality of services mostly developed on Likert's scale. The carried out research of examining university students' satisfaction will make it possible to present methodological aspects of this method.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 86, s. 194-205